2018
DOI: 10.1073/pnas.1707663115
|View full text |Cite
|
Sign up to set email alerts
|

Targeted knockout of a chemokine-like gene increases anxiety and fear responses

Abstract: SignificanceEmotion-related responses, such as fear and anxiety, are important behavioral phenomena in most animal species, as well as in humans. However, the underlying mechanisms of fear and anxiety in animals and in humans are still largely unknown, and anxiety disorders continue to represent a large unmet medical need in the human clinic. Animal models may speed up discovery of these mechanisms and may also lead to betterment of human health. Herein, we report the identification of a chemokine-like gene fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 59 publications
(95 reference statements)
0
44
0
Order By: Relevance
“…Zebrafish is a shoaling species, and, in nature, CAS is expected to function in shoals. As such, increased shoaling responses are consistently observed during CAS exposure (Table 1; Speedie & Gerlai, 2008;Lima et al, 2016;Canzian et al, 2017;Choi et al, 2017).…”
Section: /41mentioning
confidence: 90%
See 1 more Smart Citation
“…Zebrafish is a shoaling species, and, in nature, CAS is expected to function in shoals. As such, increased shoaling responses are consistently observed during CAS exposure (Table 1; Speedie & Gerlai, 2008;Lima et al, 2016;Canzian et al, 2017;Choi et al, 2017).…”
Section: /41mentioning
confidence: 90%
“…Shoaling Zebrafish ↑ (Speedie & Gerlai, 2008;Lima et al, 2016;Canzian et al, 2017;Choi et al, 2017) Fathead minnows…”
Section: Not Testedmentioning
confidence: 99%
“…[62,63]. These tests have also been used to study the neural mechanisms of anxiety-like behavior [64][65][66][67][68]. Thus, these tests can be used both as screening tests and as behavioral bioassays.…”
Section: Behavioral Models In Zebra Fishmentioning
confidence: 99%
“…Interestingly, among these differentially expressed genes, we found that chemokine receptors, including cxcr3.2 and cxcr4b, were significantly uprelugated in olfactory mucosae. Recent study has found that the chemokine-like gene family, samdori (sam), especially gene sam2, plays an important role in fear response in zebrafish (Choi et al, 2018). Another important gene, v2rl1, which is a ubiquitously expressed receptor in vertebrate olfactory system (DeMaria et al, 2013;Wakisaka et al, 2017), showed significant downregulation after fright reaction.…”
Section: Broad-scale Differences Of Gene Expression In Zebrafish Aftementioning
confidence: 99%